Closed loop symbol synchronizers - Reis, António D. (2002)
In this paper, we present four types of closed loop symbol synchronizers, namely the analog, the hybrid, the combinational and the sequential. In the phase synchronizers the difference between the varioustypes was inside the phase comparator, with a similar mode inthe symbol synchronizers this difference is inside the signalcomparator. Our main objective is to study the jitter behavior, of the various synchronizers, in the noise presence and then to establish some comparisons.